Prototype Implementation of a Scalable Real-Time Dynamic Carpooling and Ride-Sharing Application (Informatica, 2014)
Setting out to build a real-time carpool and ride-sharing solution, which would be able to attain a global user base and is initially designed as highly-scalable, this paper describes some of the selected designed concepts, distribution and cloud computing strategies needed to do so. Our selections were based on experiences of others with same or similar-purpose solutions which were developed in the previous decade. Some of these solutions were either outdated, mostly by leaving its users with a subpar user experiences as their user base grew, or outgrown by having limited client reach, leaving them available only to a small portion of mobile client devices or desktop browsers and users. This paper presents an implementation of a ridesharing application prototype that follows all of aforementioned strategies. The goal of this prototype is to show that it is possible to make very scalable and ubiquitous ridesharing application, which is able to successfully reach and serve a global user base.